Practice the problems of Math in Focus Grade 4 Workbook Answer Key Chapter 6 Practice 6 Renaming Whole Numbers when Adding and Subtracting to score better marks in the exam.
Math in Focus Grade 4 Chapter 6 Practice 6 Answer Key Renaming Whole Numbers when Adding and Subtracting Fractions
Fill in the missing numerators.
Example
Question 1.
Answer:
Explanation:
3 = 2\(\frac{6}{6}\) = 2 + 1.
= 1\(\frac{12}{6}\) = 1 + (12)6 = 1 + 2.
= \(\frac{18}{6}\)
Question 2.
Answer:
Explanation:
2\(\frac{7}{9}\) = 1\(\frac{16}{9}\)
= \(\frac{25}{9}\)
Add. Express each answer as a mixed number in simplest form.
Question 3.
\(\frac{4}{9}\) + \(\frac{2}{3}\)
Answer:
\(\frac{4}{9}\) + \(\frac{2}{3}\) = 13 ÷ 9 or \(\frac{13}{9}\)
Explanation:
\(\frac{4}{9}\) + \(\frac{2}{3}\)
= (4 + 6) ÷ 9
= 13 ÷ 9 or \(\frac{13}{9}\)
Question 4.
\(\frac{1}{6}\) + \(\frac{11}{12}\)
Answer:
\(\frac{1}{6}\) + \(\frac{11}{12}\) = 13 ÷ 12 or \(\frac{11}{12}\)
Explanation:
\(\frac{1}{6}\) + \(\frac{11}{12}\)
= (2 + 11) ÷ 12
= 13 ÷ 12 or \(\frac{11}{12}\)
Question 5.
\(\frac{1}{4}\) + \(\frac{3}{8}\) + \(\frac{3}{4}\)
Answer:
\(\frac{1}{4}\) + \(\frac{3}{8}\) + \(\frac{3}{4}\) = 11 ÷ 8 or \(\frac{11}{8}\)
Explanation:
\(\frac{1}{4}\) + \(\frac{3}{8}\) + \(\frac{3}{4}\)
= (2 + 3) ÷ 8 + \(\frac{3}{4}\)
= \(\frac{5}{8}\) + \(\frac{3}{4}\)
= [5 + 6] ÷ 8
= 11 ÷ 8 or \(\frac{11}{8}\)
Question 6.
\(\frac{4}{5}\) + \(\frac{7}{10}\) + \(\frac{9}{10}\)
Answer:
\(\frac{4}{5}\) + \(\frac{7}{10}\) + \(\frac{9}{10}\) = 12 ÷ 5 or \(\frac{12}{5}\)
Explanation:
\(\frac{4}{5}\) + \(\frac{7}{10}\) + \(\frac{9}{10}\)
= (8 + 7) ÷ 10 + \(\frac{9}{10}\)
= \(\frac{15}{10}\) + \(\frac{9}{10}\)
= (15 + 9) ÷ 10
= \(\frac{24}{10}\)
= 12 ÷ 5 or \(\frac{12}{5}\)
Subtract. Express each answer as a mixed number in simplest form.
Example
2 – \(\frac{1}{3}\)
Method 1
2 – \(\frac{1}{3}\) = \(\frac{2}{1}\) – \(\frac{1}{3}\)
= \(\frac{6}{3}\) – \(\frac{1}{3}\)
= \(\frac{5}{3}\) = 1\(\frac{2}{3}\)
Metgod 2
2 – \(\frac{1}{3}\) = 1\(\frac{3}{3}\) – \(\frac{1}{3}\)
= 1\(\frac{2}{3}\)
Question 7.
3 – \(\frac{5}{6}\) – \(\frac{1}{3}\)
Answer:
3 – \(\frac{5}{6}\) – \(\frac{1}{3}\) = \(\frac{5}{2}\)
Explanation:
3 – \(\frac{5}{6}\) – \(\frac{1}{3}\)
= 3 – [(5 – 2) ÷ 6]
= 3 – \(\frac{3}{6}\)
= (18 – 3) ÷ 6
= \(\frac{15}{6}\)
= \(\frac{5}{2}\)
Question 8.
2 – \(\frac{1}{4}\) – \(\frac{1}{4}\)
Answer:
2 – \(\frac{1}{4}\) – \(\frac{1}{4}\) = 2.
Explanation:
2 – \(\frac{1}{4}\) – \(\frac{1}{4}\)
= 2 – (0)
= 2.
Question 9.
2 – \(\frac{2}{7}\) – \(\frac{3}{14}\)
Answer:
2 – \(\frac{2}{7}\) – \(\frac{3}{14}\) = \(\frac{27}{14}\)
Explanation:
2 – \(\frac{2}{7}\) – \(\frac{3}{14}\)
= 2 – [(4 – 3) ÷ 14]
= 2 – \(\frac{1}{14}\)
= (28 – 1) ÷ 14
= \(\frac{27}{14}\)
Question 10.
3 – \(\frac{7}{10}\) – \(\frac{3}{4}\)
Answer:
3 – \(\frac{7}{10}\) – \(\frac{3}{4}\) = \(\frac{61}{20}\)
Explanation:
3 – \(\frac{7}{10}\) – \(\frac{3}{4}\)
= 3 – {[(2 × 7) – (3 × 5)] ÷ 20}
= 3 – [(14 – 15) ÷ 20]
= 3 – (-1 ÷ 20)
= 3 + \(\frac{1}{20}\)
= (60 + 1) ÷ 20
= \(\frac{61}{20}\)